Ngưỡng quy mô tối ưu của doanh nghiệp Việt Nam - Trần Thị, Bích; Đỗ Văn, Huân (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study investigates the optimal firm size in Vietnam. Using data from the enterprise census in 2016 and 2020, the study shows that the optimal firm size in Vietnam is small, at 50–99 employees in 2016 and 25–49 employees in 2020. Though the proportion of firms under the optimal size has decreased, the share is still high at over 70% in 2020. The analysis reveals that the optimal firm size varies by industry and region. The service sector has a small optimal firm size while the medium- and high-tech manufacturing industries have an optimal firm size of up to 1000 employees. However, firms in manufacturing industries account for only 8%. Results from the study imply that to promote productivity and economic growth, Vietnam needs to design and implement policies supporting businesses to grow to their optimal size. Furthermore, it should restructure the economy to increase the manufacturing sector share in order to catch up with developed countries.